Group Formation Using Friendship Graph in Managing Students’ Projects in Educational Settings - et.al, Ochilbek Rakhmanov (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the literature, there are several group formation methods such as random, self-selected, instructor-selected, and mixed, which have been outlined on how to form groups for effective learning and project completion. There is little empirical research on which of the approaches creates the best student learning experience. In this article, we examine the use of acquaintance and friendship graphs in generating groups to manage projects in a learning environment. This work focuses on freshmen and sophomores from faculty of Natural and Applied Sciences and faculty of Medicine at “Nile university of Nigeria”. In creating the friendship graphs for each of the classes, a questionnaire is employed. The responses from the students are transformed into graph input data. The resultant graphs are then analyzed to create the project groups. The performance (measured by group grades) of students in the projects is an evidence that this method of creating groups is effective. Moreover, the project completion time and average score of the projects show improvement in comparison to previous year’s groups, which were formed by instructor-selected method. Furthermore, testing our created groups against the normal standard of group formation using a balanced distribution of GPA scores, see [1], indicates that our method passed with 83%. In fact, when each student was presented with the opportunity to choose through voting whether to be within an instructor-selected group with a balanced distribution of GPA scores or a group formed by the friendship graph approach, an overwhelming 78% chooses the latter